Social Service in Germany and it’s foundations - Duarte, Katja Klebsattel; SBraga, Cilene ebastiana da Conceição (Argumentum, 2022)
This article approaches the central moments in the historical development of Social Service in Germany. The aim is to present the institutions that organize the profession, and to address the theoretical-methodological trends in German Social Work. It deals with the genesis of German Social Work, the profession under National Socialism, its critical theoretical trends in the 1960s and its current theoretical-methodological composition. Data collection took place through a state-of-the-art survey of German bibliographies on the subject.  It is noteworthy that contemporary German Social Work is characterized by the influence of several theoretical trends and does not represent a hegemonic professional project.